Frameworks for smart grid cyber security analysis - Gündüz, Muhammed Zekeriya; Demirol, Doygun; Daş, Resul; Hanbay, Kazım (Elsevier, 2024)
This chapter provides an in-depth examination of the comprehensive framework essentials for analyzing cybersecurity in smart grid applications. It covers crucial components necessary to maintain the integrity and resilience of smart grid systems. The chapter begins with a focus on authentication and access control measures to ensure secure communication flows within the system. Robust mechanisms to authenticate and authorize users and devices accessing smart grid infrastructures are emphasized. The chapter further explores the importance of deploying pervasive attack detection and countermeasures throughout the smart grid, emphasizing proactive mitigation of cyber threats to protect critical assets. Additionally, it explores the importance of implementing basic and lightweight cryptographic functions at the node level to secure transactions and communications. The security of network protocols, from the application layer to the MAC layer, is thoroughly examined, identifying vulnerabilities and strategies for enhancing security at each protocol layer. Furthermore, the chapter highlights the utility of cyber security testbed platforms for investigating vulnerabilities within power infrastructures, providing controlled environments for simulating attacks, and evaluating security measures. Finally, a related case study of the National Institute of Standards and Technology (NIST) is integrated to offer practical insights into applying the framework in real-world scenarios, with implications for researchers, practitioners, and policymakers involved in enhancing smart grid cyber security. © 2025 Elsevier Inc. All rights reserved.
Keywords: Access control; Authentication; Cyber security; Cyber security testbeds; Threat analysis